Etika Dakwah dalam Kasus Pelecehan Seksual Gus Elham: Analisis Perspektif Moral dan Sosial - Anizar Maulana Ibrahim; Ashadiva Dinanti Puteri; Ahmad Ridho; Alif Musyafa Karim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study is motivated by the emergence of public controversy surrounding the alleged sexual harassment case involving the preacher Gus Elham, which has sparked widespread debate about ethical boundaries in da’wah activities. This phenomenon reflects a moral and social crisis in contemporary da’wah practices, particularly in relation to power relations, child protection, and the moral responsibility of religious figures as public role models. This study aims to analyze violations of da’wah ethics in this case from moral and social perspectives, as well as to identify its impact on public trust in preachers and religious institutions. The method used is a descriptive qualitative approach through the analysis of online news, public statements, social media posts, interview recordings, and da’wah-related content associated with the case. The findings indicate that the actions in question not only violated norms of decency but also revealed a failure to understand principles of child protection and ethics of da’wah based on akhlakul karimah. Socially, the case demonstrates a moral crisis affecting religious authority and an increase in public skepticism toward religious figures. The implications of this study emphasize the importance of formulating stricter da’wah codes of ethics, strengthening ethical literacy among preachers, and integrating child protection values into da’wah practice to prevent similar cases from recurring.